Penerapan Engine Simulator Pada Program Studi Teknika - Yudi, Muhammad Fauzi (Pusdikra Publishing, 2023)
In this era, technology is growing rapidly, the use of technology is increasingly being felt in all fields, one of which is in the field of education. The teaching and learning process is the core of the overall educational process with the teacher as the main role holder. Many teaching and learning events are rooted in various views and concepts. Therefore the embodiment of the teaching and learning process can occur in various models. The teaching and learning process is a process of mutual interaction between teachers and students in educative situations to achieve certain goals. Meanwhile, to provide material regarding machinery in shipping is certainly very difficult and does not present the physical form of the machine itself, therefore a combination of learning methods using engine simulator applications and theoretical understanding is certainly very helpful for cadets in understanding the material presented. The Engineering Study Program has an Engine Simulator Laboratory which can be used as a learning medium for Cadets of the Akademi Maritim Belawan (AMB) Medan.